Establishing a Luminescence-Based Chronostratigraphy for the Last Glacial-Interglacial Cycle of the Loess-Palaeosol Sequence Achajur (Armenia) - Lomax, Johanna; Wolf, Daniel; Wolpert, Urs Tilmann; Sahakyan, Lilit; Hovakimyan, Hayk; Faust, Dominik; Fuchs, Markus (Frontiers in Earth Science, 2021)
The loess-palaeosol section Achajur is part of the Sevkar loess area in north-eastern Armenia and comprises three prominent pedocomplexes with intercalated loess units, probably spanning at least three glacial-interglacial cycles. With its central position between the Black Sea and the Caspian Sea, the Sevkar loess area serves as important bridge between loess sections in southeastern Europe and Central Asia. Establishing a numerical chronology of the Achajur loess section enables correlation with other loess-palaeosol sections and a palaeoenvironmental reconstruction of the region. In this paper, we focus on the chronology of the last glacial-interglacial cycle using luminescence dating on fine grain (4–11 µm) material. We compare two post-IR-IRSL protocols on polymineral fine grain using different stimulation temperatures, in order to evaluate the influence of fading and potential unbleachable residuals on our samples. For a backup of the younger ages (<50 ka), we also applied a single aliquot protocol on the quartz fine grain fraction. The results indicate that the upper loess unit was deposited during MIS3 and 4, while MIS2 ages are not present. The underlying pedocomplex and loess unit fall into MIS5 and MIS6, respectively. This confirms that the loess was deposited during dry phases and pedocomplexes formed during wetter phases, as is also shown by comparison with other palaeoenvironmental proxies from the area.